(untitled) (The Research of Medical Science Review, 2025)
Purpose: The present review is designed to investigate the efficacy of AgNPs as an adjunct treatment of antimicrobial therapy for periodontitis. Methodology: A systematic review was done on electronic databases, including Google Scholar, Science Direct, and PubMed. Articles retrieved included in vitro, clinical, and cross-sectional studies with relevance. This further narrowed down the selection process by applying the PRISMA methodology. Results: This study reveals that AgNPs possess robust antibacterial activity against periodontal pathogens. At the correct concentrations, they can halt bacterial multiplication and are equally effective as standard drugs like tetracycline. In vivo studies prove that AgNPs augmented traditional treatments for improvement in periodontal health. Conclusion: Silver nanoparticles possess potential adjunctive therapies for periodontitis as they display an antimicrobial effect. Their long-term safety and efficacy have yet to be well established in many studies, however.